From human trafficking to modern slavery: the development of anti-trafficking policy in the UK - Broad, Rosemary (European journal on criminal policy and research, 2019)
The UK Modern Slavery Act 2015 is the first national legislation to use the term ‘modern slavery’ and to explicitly target ‘slavery’ as opposed to ‘human trafficking’, ‘forced labour’, or other terms. This article explains the development of UK modern slavery policy, which did not arise as a rational response to a defined problem, but has gradually emerged from the policy process as a moderately structured problem. Problem structuring took place in two phases. The first phase was marked by a series of problematisations and policy responses, with disjunctions between the constructed policy problem and the social problem. Elite problematisations excluded alternatives, although the final shape of policy remained open. Policy built up incrementally, running ahead of research so that the policy frame was limited to sexual exploitation while marginalising labour exploitation concerns. In the second phase, unresolved problems of legislation were questioned under the influence of a new moralistic policy frame, an international discourse on slavery, supported by elite political actors. Campaign groups and licit industry also became more influential, increasing the policy scope to take in more types of exploitation. This generated a second round of legislative problematisation, ultimately embedded in the Modern Slavery Act 2015. The two-phase process and prevailing top-down policy direction worked against human rights discourses and victim protection. Modern slavery remains a moderately structured problem, with more work necessary to address unintended consequences and implementation difficulties, including enhancing multi-agency working.